Characteristics and failure mechanisms of the Sieidi unstable rock slope - Kaltenrieder, Fabrice (UiT Norges arktiske universitet, 2024)
Seidi is an unstable rock slope at the western end of the Sørfjord in Tromsø municipality, Troms County, northern Norway. It displays clear signs of rock slope deformation: an offset at the crest, multiple scarps, talus and loose material and a bulging slope. The objective of this work is to interrogate the failure mechanics in order to determine the degree of control lithology and bedrock structure have on the slope deformation and identify the underlying and kinematics and their influence on the deformation patterns of the Sieidi unstable rock slope. This thesis outlines a multifaceted approach to the analysis of the kinematics, structural properties, and failure mechanisms of the Sieidi unstable rock slope (URS)in Troms County, northern Norway. The analysis of the Sieidi URS is based on 2D InSAR displacement rates, morphological observation, 416 structural measurements, and the analysis of 25 thin sections. It elaborates on how structural discontinuities, namely schistosity planes and joint sets, are decisive factors of rock slope stability. Moreover, it accentuates the importance of the anisotropy of the rock since the microcracks form along the schistosity plane S1, which represents the main weakness zone in the rock mass that controlles the fracture propagation. It concludes clearly that the schistosity plane S1 (9°/246°) and joint sets denote the preeminent pathway for fracturing and failure propagation by interconnecting the schistosity and joint planes, leading to stepped fractures. The kinematic interpretation postulates a complex morpho-structural geometry with a translational basal failure mechanism with a convoluted component augmenting spatially towards the south. The rear rupture surface is controlled by joint set 1 (80°/103°), whereas the main morphological features, the major scrapes, are controlled by joint set 2 (89°/335). The observed joint sets play an essential role in weakening slope strength, deforming the slope and forming a basal and rear rupture surface. The unstable area, which has ...